Levantamiento geológico estructural de la vía Intervalles de la abscisa 13+300 a 16+400 del barrio la Merced, parroquia el Tambo, cantón Catamayo, provincia de Loja. - Jiménez Estrella, Adrián Fernando (2022)
The present research work "Structural geological survey of the Intervalles road from the abscissa 13 + 300 to 16 + 400 of the La Merced neighborhood, El Tambo parish, Catamayo canton, Loja province" has a route of 3.1km, a total area of 64.1ha of extension and is destined to the elaboration of a structural geological map at a scale of 1: 5,000 to 100m on each side of the axis of the road in order to analyze the lithological units and geological structures present throughout this territory, to At the same time, an inventory of the existing landslides on the ground was carried out. The investigation began with obtaining the geological information of the sector through Geological Sheet 57 GONZANAMÁ (CT-NVII-B series J62-G at 1: 100,000 scale) in order to have an idea of the materials present on the ground, later We arrived at the study site and ten geodetic control points were placed along the study path and then carried out a topographic survey of the land with the help of photogrammetry, where the drone in charge of the company SETIA GROUP made two plans flight of twenty-two minutes each, thus capturing 250 photos per flight, in turn providing contour lines at 1m from the ground and an ortho-photo with 2.5 x 2.5cm resolution of the entire territory for a better visualization of the area . Once the topography of the sector was obtained, the survey and location of the outcrops present in the site continued, taking the structural data from them and identifying the materials found to verify them with the regional geology, at the same time the structures were located geological such as faults and folds to take note of their reservoir elements and thus have detailed information on these through outcrop files and rock descriptions. In the case of the geomorphology of the site, we started from the orthophotos obtained together with the information from the Plan of Development and Territorial Ordering of El Tambo 2014-2019 in order to make a map of the geoforms sighted in situ. With the geomorphology obtained, it was possible to make the slope map, which indicates the inclination of the existing elevations and is cataloged according to their angle as indicated by Demek (1972). The lithostratigraphy was carried out according to the outcrops sighted, since with this information obtained in the field, the stratigraphic columns were made to give greater detail to the materials present along the study pathway. For the landslide inventory, we started from the photointerpretation of the ortho-photos obtained from the photogrammetry and the possible landslides were visually located for later corroborating them in the field, once the information was obtained, a mass movement form was filled out, where their status is described in detail. Once all the work in the field was done, the structural geological map was made at a scale of 1: 5,000, for this it was necessary the ArcGIS 10.3 software and the data of all the aspects mentioned above in order to enter them into the program and delineate symbology and legend thereof, in turn a cross-sectional geological section was made of the most prominent area of the road for greater detail of the terrain. Keywords: Structural geology, photogrammetry, drone photography, landslide inventory, lithological unit, geological structure.